P356 An aeromycological study of diagnostic microbiology laboratory at a tertiary care center. (20th September 2022) - Gupta, Mansi; Rastogi, Vijaylatha; Verma, Pushpanjali; Tak, Kiran; Chaudhary, Meenu; Chaturvedi, Parul; Parihar, Geeta
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objectives: To evaluate the aeromycoflora of diagnostic microbiology laboratory at a tertiary care center. Methods: This is an ecological prospective analytical study. This pilot study was conducted at a diagnostic microbiology laboratory in which the Bacteriology section and Mycology section were the study areas. One indoor and one outdoor community area were taken as community controls and histopathology lab was taken as Laboratory control. The sampling was done every fortnight for a period of 1 year from March 2021 to February 2022. Environmental air samples were collected using the passive settle plate method based on sedimentation on 90 mm Sabouraud Dextrose Agar plates. The plates were exposed for 30 mins at a height of 1 m and a distance of 1m from the wall as per standard references. After sample collection, plates were incubated at 22 ° C for a maximum of 3 weeks or till the time the colonies were countable. The colonies were counted and the total CFU/m3 was calculated using the Omeliansky Formula. The identification of the isolates was done using standard mycological protocols. Statistical analysis using paired student t -test was also performed. Results: A total of 13 types of fungi were isolated in the study belonging to the following genera- Aspergillus, Alternaria, Curvularia, Bipolaris, Cladosporium, Fonseacea, Fusarium, Penicillium, and Rhizopus . In the Bacteriology section, the highest frequency was of A. niger (63%) followed by A. flavus (50%) while in the mycology section the highest frequency of A. fumigatus (50%) followed by A. flavus (46%) was observed. Certain fungal species known to cause serious infections like A. flavus, Rhizopus arrhizus, Fusarium spp., Penicillium spp., Curvularia spp., were isolated only in the laboratory environment and were absent in the Community Controls. The total CFU/m3 ranged from 26.11 to 576.64 in mycology section and 26.11 to 419.37 in Bacteriology section while in the indoor community control the range was between 26.11 to 235.89 CFU/m3 which was found to be statistically significantly lesser using T-test when compared to the laboratory environment. A seasonal variation with higher counts during the autumn months (September-October) was observed in both the labs. Seasonal variation in the distribution of fungi was observed especially in the case of Rhizopus . Conclusion: Healthcare workers spending a significant time in this environment need to be made aware of the quality of air in laboratories and initiation of appropriate intervention to make the laboratory environment safer to work as in this study it was found that more pathogenic fungi were grown in a laboratory environment which is clearly due to the processing of clinical samples in labs as compared to the community environment. The use of standard aseptic precautions, biosafety cabinets, fumigation of laboratories, and regular housekeeping activities would help to decrease the aerosols generated in the labs. The results from this study will be useful to spread awareness and help in formulating guidelines for the air quality of laboratories. However, aeromycology data from more such studies over a larger number of labs from different demographic areas are needed to enable a better understanding of the role of the formulation of standards for a safer laboratory environment.